The transmission of monetary policy to the cost of hedging - Matthias Fengler; Winfried Koeniger; Stephan Minger (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
We analyze the transmission of monetary policy to the costs of hedging using options order book data. Monetary policy transmits to hedging costs both by changing the relevant state variables, such as the value of the underlying, its volatility and tail risk, and by affecting option market liquidity, including the bid-ask spread and market depth. Our estimates suggest that during the peak of the pandemic crisis in March 2020, monetary policy decisions resulted in substantial changes in hedging costs even within short intraday time windows around the decisions, amounting approximately to the annual expenses of a typical equity mutual fund.
Keywords: G13; G14; D52; E52; 330; Liquidity; Monetary policy; Option order books; Option markets; COVID-19 pandemic